Keberadaan Objek Wisata Bahari Pulau Merak Kecil Dalam Menunjang Perekonomian Masyarakat Desa Mekarsari, Pulomerak Cilegon Banten - Siti Humayroh; Angga Pusaka Hidayat (Publikasi Berkala Pendidikan Ilmu Sosial, 2024)
This research is motivated by the physical condition of Indonesia which offers its own advantages for tourists. Indonesia has abundant natural wealth. These natural resources are directly related to the way society uses them to generate wealth. The tourism business, which is currently developing rapidly and has established itself as a large industry in many countries, is a driving force that influences people's income and other economic factors. There will be many benefits for the local community if the tourist attractions there are managed in the right way. The role of the Merak Kecil Island tourist attraction in improving the standard of living of the residents of Mekarsari Village, Cilegon, Banten is the main subject of this research. The community around the popular tourist destination Merak Kecil Island was used as research subjects in this study, which used qualitative research methods. Interviews, observation and documentation are the methods used in data collection. To ensure that the data collected is beyond doubt, the researcher uses source, technical, and temporal triangulation to verify the authenticity of the data. Research findings show that this tourist destination is managed locally and in line with POAC principles (planning, organizing, mobilizing and controlling). The potential of Merak Kecil Island as a tourist destination lies in its stunning sea views. The presence of the Merak Kecil Island tourist attraction in Mekarsari Village is considered to have a significant influence in increasing income levels because it provides a platform for the community to carry out various economic activities.